Mandatory Reporting (MR) in Higher Education: College Students' Perceptions of Laws Designed to Reduce Campus Sexual Assault. (June 2016) - Mancini, Christina; Pickett, Justin T.; Call, Corey; Roche, Sean Patrick
Mandatory reporting (MR) policies concerning sexual assault victimization now extend to institutions of higher education. The laws are new and thus controversial since relatively little investigation into their impact has occurred. Additionally, since the laws require disclosure to police, at times, even in instances where victims object, opponents have expressed concerns about potential unintended effects, such as diminished victim autonomy. Perhaps, though, the most glaring question involves how college students perceive the policies. Because students are the focus of the laws, this investigation evaluates student opinion about MR, including approval for the policy, the likelihood of personally reporting under MR, perceptions of faculty compliance, and expected outcomes of MR laws. Findings suggest overwhelming support for MR, substantial likelihood of personally reporting assault under the law, and strong belief in faculty compliance. Not least, although students recognize both the positive and negative possibilities of the law, higher percentages believed in the law's potential benefits (e.g., increase university accountability). Implications for research and policy are discussed.